2011
DOI: 10.1007/s10753-011-9303-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urinary Trypsin Inhibitor on Lipopolysaccharide-Induced Acute Lung Injury in Rabbits

Abstract: This study was undertaken to clarify the effects of urinary trypsin inhibitor (UTI) on lipopolysaccharide (LPS)-induced acute lung injury. Rabbits were randomly assigned to one of seven groups: saline only, UTI, LPS, pre- or post-UTI-high (infusion of UTI of 25,000 U/kg followed by 25,000 U/kg over 2 h), pre- or post-UTI-low (infusion of UTI of 2,500 U/kg followed by 2,500 U/kg over 2 h). UTI was administered 30 min before (pre-groups) or 15 min after (post-groups) LPS administration. Rabbits were mechanically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…However, since the onset of CA is unpredictable, hypoxic preconditioning is not applicable for patients experiencing CA. UTI, a urinary trypsin inhibitor, has been shown to possess anti-inflammatory properties and attenuate LPS-induced acute lung injury (10), inhibit systemic inflammatory responses resulting from pulmonary I/R (11) and alleviate pulmonary I/R injury via the inhibition of TNF-α expression in rats (17). In addition, previous studies have demonstrated that UTI suppresses the elevation of IL-6 and IL-8 levels in patients undergoing coronary artery bypass grafting under extracorporeal circulation (18), alleviates forebrain I/R injury by inhibiting the production of superoxide radicals and intercellular adhesion molecule-1 (19) and improves oleic acid-induced acute lung injury by reducing TNF-α levels and inducing leukocyte activation (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, since the onset of CA is unpredictable, hypoxic preconditioning is not applicable for patients experiencing CA. UTI, a urinary trypsin inhibitor, has been shown to possess anti-inflammatory properties and attenuate LPS-induced acute lung injury (10), inhibit systemic inflammatory responses resulting from pulmonary I/R (11) and alleviate pulmonary I/R injury via the inhibition of TNF-α expression in rats (17). In addition, previous studies have demonstrated that UTI suppresses the elevation of IL-6 and IL-8 levels in patients undergoing coronary artery bypass grafting under extracorporeal circulation (18), alleviates forebrain I/R injury by inhibiting the production of superoxide radicals and intercellular adhesion molecule-1 (19) and improves oleic acid-induced acute lung injury by reducing TNF-α levels and inducing leukocyte activation (20).…”
Section: Discussionmentioning
confidence: 99%
“…One hour after an LPS challenge, activin A-containing cells and neutrophil precursors in the bone marrow were greatly reduced in number, and activin A-containing neutrophils appeared throughout the lung. Preferential translocation of neutrophils from the bone marrow to the lungs is a characteristic feature of LPS-induced inflammation and is responsible for lung damage in such models (1,3,31,33). Neutrophils previously have been implicated as a source of activin A in lung inflammation following allergen challenge in humans (14).…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that UTI, as a broad-spectrum anti-inflammatory substance, may significantly down-regulate the production of IL-8 (Cao et al 2010). Bae, H. B. et al (Bae et al 2011) discovered the level of IL-8 in the UTI preconditioning sepsis rats is significantly lower than those in sepsis rats without treatment, and associated pathological section, they hold the opinion that UTI may through inhibiting IL-8 and so on mediators of inflammation in septic rats to act as a protective role in the septic process. Also there is evidence which shows that UTI can suppress the expression of IL-8 in vitro (Nakamura et al 1997) …”
Section: Inhibit Releasing Of Il-8 To Act As Protective Actionmentioning
confidence: 99%